Ancestral neural circuits potentiate the origin of a female sexual behavior in Drosophila - Li, Minhao; Chen, Dawn S.; Junker, Ian P.; Szorenyi, Fabianna I.; Chen, Guan Hao; Berger, Arnold J.; Comeault, Aaron A.; Matute, Daniel R.; Ding, Yun (Nature communications, 2024)
Courtship interactions are remarkably diverse in form and complexity among species. How neural circuits evolve to encode new behaviors that are functionally integrated into these dynamic social interactions is unknown. Here we report a recently originated female sexual behavior in the island endemic Drosophila species D. santomea , where females signal receptivity to male courtship songs by spreading their wings, which in turn promotes prolonged songs in courting males. Copulation success depends on this female signal and correlates with males’ ability to adjust his singing in such a social feedback loop. Functional comparison of sexual circuitry across species suggests that a pair of descending neurons, which integrates male song stimuli and female internal state to control a conserved female abdominal behavior, drives wing spreading in D. santomea . This co-option occurred through the refinement of a pre-existing, plastic circuit that can be optogenetically activated in an outgroup species. Combined, our results show that the ancestral potential of a socially-tuned key circuit node to engage the wing motor circuit facilitates the expression of a new female behavior in appropriate sensory and motivational contexts. More broadly, our work provides insights into the evolution of social behaviors, particularly female behaviors, and the underlying neural mechanisms. How do neural circuits evolve to encode new social behaviors? Here we show that in Drosophila santomea , females signal their sexual receptivity by spreading wings in response to male songs, and this recently originated social behavior evolved through the actualization of a pre-existing latent circuit.